2013
DOI: 10.2106/jbjs.k.01032
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Plantar Pressure and Talonavicular Alignment to Lateral Column Lengthening in Flatfoot Reconstruction

Abstract: The lateral column should be lengthened judiciously, as a 2-mm difference leads to significant difference not only in angular correction of the talonavicular joint but also with regard to pressure in the lateral aspect of the forefoot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
81
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 39 publications
8
81
1
Order By: Relevance
“…We found that the pressure of the medial column increased significantly, while that of the lateral column decreased after the establishment of the flatfoot model, which was statistically different from the intact foot. As the graft increased incrementally, lateral plantar pressures increased gradually and medial plantar pressures decreased at the same time, similar to the results of prior studies on the Evans osteotomy [10, 19, 20]. In this study, the pressure of the lateral column was approximately equal to that of the intact foot with a 2 mm LCL, while the pressure of the medial column was 34.7 kPa, which showed no statistical difference compared with the flatfoot condition.…”
Section: Discussionsupporting
confidence: 88%
“…We found that the pressure of the medial column increased significantly, while that of the lateral column decreased after the establishment of the flatfoot model, which was statistically different from the intact foot. As the graft increased incrementally, lateral plantar pressures increased gradually and medial plantar pressures decreased at the same time, similar to the results of prior studies on the Evans osteotomy [10, 19, 20]. In this study, the pressure of the lateral column was approximately equal to that of the intact foot with a 2 mm LCL, while the pressure of the medial column was 34.7 kPa, which showed no statistical difference compared with the flatfoot condition.…”
Section: Discussionsupporting
confidence: 88%
“…Davitt and Morgan also reported two cases of stress fractures of the fifth metatarsal following Evans’ calcaneal lengthening procedure 3 . Oh et al (2013) demonstrated the effects of different amounts of LCL on lateral plantar pressures of the foot 15 . They found significantly decreased talonavicular uncoverage and increased lateral column plantar pressures as they increased the amount of LCL performed from 6 mm to 10 mm 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Oh et al (2013) demonstrated the effects of different amounts of LCL on lateral plantar pressures of the foot 15 . They found significantly decreased talonavicular uncoverage and increased lateral column plantar pressures as they increased the amount of LCL performed from 6 mm to 10 mm 15 . These studies suggest that overcorrection of the abduction deformity in patients with stage II AAFD may lead to inferior clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It is challenging to assess hindfoot alignment intraoperatively, and surgeons often elect to perform the MCO first to achieve the ideal hindfoot alignment before performing the LCL to correct the midfoot deformity. While patients are often satisfied with these procedures, overcorrection and pain still occur, 8,13 and care should be taken when combining LCL and MCO procedures. Our results support a change in operative planning, to first correct the midfoot deformity with a LCL followed by performing the MCO to achieve ideal hindfoot alignment.…”
Section: Discussionmentioning
confidence: 99%